Providers’ knowledge and perception of xylazine in the unregulated drug supply: a sequential explanatory mixed-methods study - Hill, Katherine; Minahan-Rowley, Rebecca; Biegacki, Emma T.; Heimer, Robert; Sue, Kimberly L. (Harm reduction journal, 2024)
Xylazine is increasingly prevalent in the unregulated opioid supply in the United States. Exposure to this adulterant can lead to significant harm, including prolonged sedation and necrotic wounds. In the absence of literature describing healthcare providers' experiences with treating patients who have been exposed to xylazine, we aimed to explore what gaps must be addressed to improve healthcare education and best practices. From October 2023 to February 2024, we conducted a sequential explanatory mixed-methods study, with (1) a quantitative survey phase utilizing convenience sampling of healthcare providers treating patients in Connecticut and (2) a qualitative semi-structured interview phase utilizing purposive sampling of providers with experience treating patients with xylazine exposure. Summary statistics from the survey were tabulated; interview transcripts were analyzed using thematic analysis. Seventy-eight eligible healthcare providers participated in our survey. Most participants had heard of xylazine (n = 69, 95.8%) and had some knowledge about this adulterant; however, fewer reported seeing one or more patients exposed to xylazine (n = 46, 59.8%). After sampling from this subgroup, we conducted fifteen in-depth interviews. This qualitative phase revealed five themes: (1) while xylazine is novel and of concern, this is not necessarily exceptional (i.e., there are other emerging issues for patients who use drugs); (2) participants perceived that xylazine was increasingly prevalent in the drug supply, even if they were not necessarily seeing more patients with xylazine-related outcomes (XROs); (3) patients primarily presented with non-XROs, making it difficult to know when conversations about xylazine were appropriate; (4) patients with XROs may experience issues accessing healthcare; (5) providers and their patients are learning together about how to minimize XROs and reduce the sense of helplessness in the face of a novel adulterant. Xylazine-specific education for healthcare providers is currently insufficient. Improving this education, as well as resources (e.g., drug checking technologies) and data (e.g., research on prevention and treatment of XROs), is crucial to improve care for patients who use drugs.